Differential recovery of habitat use by birds after wind farm installation: A multi-year comparison. - Farfán-Aguilar, Miguel Ángel; Duarte, Jesús; Real-Giménez, Raimundo; Muñoz-Gallego, Antonio Román; Fa, Julia E.; Vargas-Yañez, Juan Mario (Elsevier, 2017)
Onshore wind farms remain one of the most widely used technologies for the production of renewable energy. These are known to affect birds through disturbance or collision. Most research focus on the impact of wind farms on raptors or other large bird species, especially those of conservation concern. However, limited information exists on the effect of wind farms on small birds. Recovery of large versus small bird populations impacted by wind farms is also largely unstudied. A reason for this is the lack of long-termdatasets based on standardized, systematic assessments. We monitored birds in the vicinity of a wind farm in an upland habitat in southern Spain (Malaga province), immediately after installation and 6.5 years post-construction. During both study periods, we observed 11 raptor and 38 non-raptor species (including 30 passerines). We found differences in recovery rates between raptors and non-raptors. Raptors showed an upturn in numbers but non-raptor abundance fell significantly. Greater attention should be paid to the recovery of wildlife after initial impact assessments than at present. This study confirms that regulatory authorities and developers should consider the likely impacts of wind farms on small bird populations. Mitigation measures focused particularly on non-raptor species should be considered and implemented as a means to reduce these negative effects.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/12531
Keywords: Aves - Efectos de la modificación del hábitat; Evaluación ecológica (Biología); Energía eólica- Impacto ambiental; Assessment collision; Bird abundances; Environmental impact; Flight behaviour; Mortality; Renewable energy